2007
DOI: 10.1111/j.1364-3703.2007.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

A potyvirus P1 protein interacts with the Rieske Fe/S protein of its host

Abstract: Yeast two-hybrid (Y2H) screens were used to test for interactions between the P1 protein of Soybean mosaic virus Pinellia isolate (SMV-P) and a cDNA expression library of its host, the aroid Pinellia ternata. Of the 13 independent interacting clones identified, ten were identical and had an open reading frame predicted to encode a 23.7-kDa protein closely related to the cytochrome b6/f complex Rieske Fe/S genes of plants. The interaction between SMV-P-P1 and the mature Rieske Fe/S protein (without transit pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…In comparison to a number of viruses in the family Potyviridae studied previously (reviewed by García-Arenal et al, 2001), SPMMV exhibited relatively high nucleotide diversity in the P1 region (Adams et al, 2005b). Data of previous studies suggest that P1 may be crucial for host adaptation in potyviruses (Shi et al, 2007;Salvador et al, 2008a). P1 proteins of potyviruses such as turnip mosaic virus and potato virus Y (PVY) have the largest v values among the mature viral proteins (at the population level), (Colinet et al, 1998) and E/P (Mukasa et al, 2003b) (broken arrows) are also shown.…”
Section: Discussionmentioning
confidence: 84%
“…In comparison to a number of viruses in the family Potyviridae studied previously (reviewed by García-Arenal et al, 2001), SPMMV exhibited relatively high nucleotide diversity in the P1 region (Adams et al, 2005b). Data of previous studies suggest that P1 may be crucial for host adaptation in potyviruses (Shi et al, 2007;Salvador et al, 2008a). P1 proteins of potyviruses such as turnip mosaic virus and potato virus Y (PVY) have the largest v values among the mature viral proteins (at the population level), (Colinet et al, 1998) and E/P (Mukasa et al, 2003b) (broken arrows) are also shown.…”
Section: Discussionmentioning
confidence: 84%
“…P1 is clearly connected with the virus host specificity and symptom manifestation (Maliogka et al, 2012;Nagyová et al, 2012b). It binds RNA and interacts with the host chloroplast Rieske Fe/S protein (Shi et al, 2007). P1 cooperates with HC-pro in the inhibition of plant posttranscriptional gene silencing (PTGS) defence and its involvement in genome amplification has been presumed, too Verchot and Carrington, 1995).…”
Section: Expression Strategy and Non-structural Proteinsmentioning
confidence: 99%
“…These changes include (1) variation in chlorophyll fluorescence and reduced chlorophyll content [3], (2) inhibition of photosynthetic activity [17], (3) disproportionate accumulation of photoassimilates [1,23], (4) alterations in chloroplast ultrastructure and functions [4,25], (5) downregulation of nuclear-encoded chloroplast and photosynthesis-related genes and proteins (CPRGs and CPRPs, respectively) [8,21,34,35], (6) direct binding of viral components with chloroplast factors [4,33], and (7) perturbation of photosynthesis by regulation of host miRNA expression [43].…”
Section: Introductionmentioning
confidence: 99%